Expression of collagenases (matrix metalloproteinase-1, -8, -13) and tissue inhibitor of metalloproteinase-3 (TIMP-3) in naturally occurring bovine cutaneous fibropapillomas - Daraban Bocaneti, Florentina; Altamura, Gennaro; Corteggio, Annunziata; Tanase, Oana Irina; Dascalu, Mihaela Anca; Pasca, Sorin Aurelian; Hritcu, Ozana; Mares, Mihai; Borzacchiello, Giuseppe (Frontiers in Veterinary Science, 2023)
Bovine cutaneous fibropapillomas are among the most common skin tumours in cattle; their etiology is associated with infection by bovine papillomavirus (BPV) types -1/-2 which are considered oncogenic. Degradation of the extracellular matrix (ECM), especially collagenolysis, is a key event during a series of relevant physiological processes, including tissue remodeling and repair. Various types of proteins are implicated in the regulation of ECM degradation: among these, matrix metalloproteinases (MMPs), a group of zinc-dependent endoenzymes, and tissue inhibitors of matrix metalloproteinases (TIMPs) are known to play a major role. Previous studies reported that aberrant expression of collagenolytic MMPs (MMP-1/-8/-13) and unbalancing between MMPs and TIMPs represent a critical step in tumour growth and invasion; however, studies regarding this topic in bovine cutaneous fibropapillomas are lacking. The aim of this study was to investigate the expression of the collagenases MMP-1/-8/-13 and TIMP-3 in naturally occurring fibropapillomas harbouring BPV-2 DNA and normal skin samples. Here, by immunohistochemistry and western blotting analysis, we demonstrated overexpression of MMP-8/-13 along with a down-regulation of MMP-1, associated with a decrease in TIMP-3 levels in tumour compared with normal skin samples. This is the first study describing MMP-1/-8/-13 and TIMP -3 expression in bovine cutaneous fibropapillomas and our results suggest that an impaired expression of collagenases along with an imbalance between MMPs/TIMPs may contribute to an increased collagenolytic activity, which in turn could be important in ECM changes and tumors development.